1984
DOI: 10.1111/j.2044-8295.1984.tb01914.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and memory

Abstract: The possible effects that sleep may have on long-term memory are first considered using the restorative hypothesis of sleep. This hypothesis proposes that protein synthesis is facilitated by sleep. The confounding role of circadian rhythms in previous sleep and memory experiments is also considered. Two experiments are reported. The first experiment investigated the effect of sleep on memory, in part using a sleep-deprivation technique. The second experiment controlled both for the interference effects and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
2

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 21 publications
4
20
0
2
Order By: Relevance
“…A facilitatory effect of sleep on the recall of previously learned items has been reported in several memory studies (Benson & Feinberg, 1975;Idzikowski, 1984;Lahl, Wispel, Willigens, & Pietrowsky, 2008) and the findings also align with demonstrations of a benefit of sleep in learning novel spoken words using recall tasks (Dumay & Gaskell, 2007Kurdziel & Spencer, 2015). Here, we found that sleep after learning appeared to prevent decay of episodic memory for the newly learned items, and eventual sleep in the AM group arrested apparent decay, with some suggestion of improved recall to a level shown by the PM group.…”
Section: Discussionsupporting
confidence: 74%
“…A facilitatory effect of sleep on the recall of previously learned items has been reported in several memory studies (Benson & Feinberg, 1975;Idzikowski, 1984;Lahl, Wispel, Willigens, & Pietrowsky, 2008) and the findings also align with demonstrations of a benefit of sleep in learning novel spoken words using recall tasks (Dumay & Gaskell, 2007Kurdziel & Spencer, 2015). Here, we found that sleep after learning appeared to prevent decay of episodic memory for the newly learned items, and eventual sleep in the AM group arrested apparent decay, with some suggestion of improved recall to a level shown by the PM group.…”
Section: Discussionsupporting
confidence: 74%
“…Many studies subsequently confirmed the positive effect of sleep on memory (63, 79, 80, 248, 341-343, 350, 408, 478, 479, 592, 745, 853, 855, 1068, 1131, 1192, 1241), examining also longer retention intervals of from 24 h up to 6 days (79,80,474,592,990). The underlying concept was that sleep acts as a "temporary shelter" that simply postpones the effect of interference and, thereby, passively maintains the memory traces (p. 717 in Ref.…”
Section: Overview Of Approaches and Conceptsmentioning
confidence: 81%
“…In this regard, electrophysiological, neurochemical, and genetic conditions are considered that will be discussed in detail in the next sections. In fact, at a purely behavioral level, numerous studies have demonstrated that sleep after learning benefits declarative (17,18,60,63,79,290,326,327,343,348,350,376,408,427,431,478,479,547,560,571,574,592,603,682,732,735,861,898,930,932,959,1069,1172,1192,1217,1274,1276,1278,1282,1302) as well as nondeclarative kinds of procedural memory (135,147,164,311,322,374,383,435,447,563,…”
Section: F the Active System Consolidation Hypothesismentioning
confidence: 99%
“…As sleep disturbances, particularly disturbed REM or slow wave sleep, have been hypothesized to impair cognitive functions, such as learning and memory consolidation [Idzikowski, 1984;Karni et al, 1994;Peigneux et al, 2001]. Mobile telephoning might also affect neuropsychological variables by causing sleep alterations.…”
Section: Introductionmentioning
confidence: 99%